2021
DOI: 10.3390/molecules26051427
|View full text |Cite
|
Sign up to set email alerts
|

Are Biogenic and Pyrogenic Mesoporous SiO2 Nanoparticles Safe for Normal Cells?

Abstract: Silicon dioxide, in the form of nanoparticles, possesses unique physicochemical properties (size, shape, and a large surface to volume ratio). Therefore, it is one of the most promising materials used in biomedicine. In this paper, we compare the biological effects of both mesoporous silica nanoparticles extracted from Urtica dioica L. and pyrogenic material. Both SEM and TEM investigations confirmed the size range of tested nanoparticles was between 6 and 20 nanometers and their amorphous structure. The cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In this way, one can determine the correlation between the percentage of hemolysis and the NaCl concentration in the solution. The test conducted here proved that, whenever a determined sodium chloride concentration is higher than that of control cells, the osmotic resistance of the red blood cells is lower, and vice versa [23,49].…”
Section: Osmotic Resistance Assaymentioning
confidence: 56%
See 1 more Smart Citation
“…In this way, one can determine the correlation between the percentage of hemolysis and the NaCl concentration in the solution. The test conducted here proved that, whenever a determined sodium chloride concentration is higher than that of control cells, the osmotic resistance of the red blood cells is lower, and vice versa [23,49].…”
Section: Osmotic Resistance Assaymentioning
confidence: 56%
“…The high-intensity band at 1060 cm −1 and the low-intensity band at 960 cm −1 were both due to vibrations of the stretching formations of Si-O and O-Si-O, a phenomenon that is typical for silica [17][18][19][20][21][22]. Two more bands were present in the spectrum of the tested silica at the wavenumbers 798 cm −1 and 452 cm −1 , and they were connected with the stretching vibrations of Si-O-Si groups and the bending vibrations of Si-O groups of siloxane groups, respectively [22][23][24]. Finally, in regard to functionalized silica, an additional band at the wavenumber 2979 cm −1 was observed, which was probably due to the vibrations of C-H stretching groups that were present in the aliphatic chains connected to the surface of the tested silica dioxides [25,26].…”
Section: Attenuated Total Reflectance Infrared Spectroscopy Technique...mentioning
confidence: 85%
“…Although many studies are devoted to deriving SiO 2 from bio-sources, to date, the knowledge on their biocompatibility profile is still underexplored. Solarska-Sciuk and colleagues [52] recently reported that the bio-silica extracted from Urtica dioica is more hazardous than the pyrogenic one in in vitro systems, pointing out the necessity to carefully assess the safety of the naturally derived SiO 2 NPs. Thus, also considering the vast variety of SiO 2 nanoforms available in the future by using the different synthesis techniques and sources, more efforts in the research aimed at characterizing their biological interactions are desirable.…”
Section: Discussionmentioning
confidence: 99%
“…At To confirm the effective production of EE2 removal systems made of nanoSiO 2 , a chitinous scaffold and HRP, an ATR-FTIR analysis has been made (Figure 3). The most intensive band with a maximum close to 1066 cm −1 unambiguously corresponds to the Si-O and Si-O-Si bonds characteristic for silica [49][50][51] or Si-O-X, where X represents ethoxy groups bonded to silicon. These signals indicated the presence of stoichiometric silicon dioxide structure [17].…”
Section: Physicochemical Characterization Of the Ee2 Removal Systemmentioning
confidence: 95%